Juridical Study of the Need for Fulfillment of the Sexual Rights of Prisoners in Class II A Correctional Institutions Bengkulu - Maryatun Maryatun; Widya Timur; Sandi Aprianto (Fakultas Hukum Dehasen, 2022)
Correctional institutions as part of the criminal justice system, namely as a coaching institution, have a very strategic role in realizing the ultimate goal of the criminal justice system, namely the rehabilitation and resocialization of lawbreakers. The research method used in this study is to use empirical legal research methods. As an empirical legal research, this research belongs to the category of descriptive-prescriptive legal research that aims to find solutions to problems (problem-solution). The problems raised in this study are (1) What is the background of the need for the fulfillment of the sexual rights of prisoners in the Class II A Bengkulu Penitentiary?, (2) What are the factors that hinder the fulfillment of the sexual rights of prisoners in the Class II A Bengkulu Penitentiary?. The results of the research and discussion are (1) The background of the need to fulfill the sexual rights of prisoners in the Class II A Correctional Institution Bengkulu because the fulfillment of the sexual needs of prisoners cannot be fulfilled naturally and normally. Relationships can take place with the cooperation or assistance of officers. For those who cannot fulfill their sexual needs in a normal/normal manner, the fulfillment is carried out in a deviant way/deviant sexual behavior. (2) The factors that hinder the fulfillment of the sexual rights of prisoners in the Class II A Correctional Institution Bengkulu are the absence of providing romance rooms for husband/wife visits privately at the Penitentiary, Prisoners cannot control their desire to perform sexual needs by using their busy schedule or participate in activities held in the Correctional Institution.